Battling dirty toilets: Singapore’s final frontiers - CHING, Rosie (Institutional Knowledge at Singapore Management University, 2019)
This case, set in June 2018, chronicles the challenges that Jack Sim, self-made millionaire and founder of the World Toilet Organisation (WTO), encountered in his decades-long quest to clean up dirty public toilets in Singapore’s coffeeshops and hawker centres. A key obstacle he faced was the lack of quantitative data on toilet cleanliness, and the means to obtain it. Moreover, the majority of coffeeshop operators were resistant to investing in toilet cleaning. In November 2015, Sim visited Rosie Ching, a senior statistics lecturer at Singapore Management University (SMU), and after lengthy discussions, Ching developed a rigorous toilet cleanliness survey and a Toilet Cleanliness Index (TCI). TCI received great attention from the media and the public, but now in early 2018, Sim was doubtful: Could Singapore’s dirty public toilets be cleaned up in the foreseeable future? Would the TCI effect a change for good and convince stakeholders of the necessity to act on the matter? This is a statistics-centric case study. Discussion of this case would enable students to apply stakeholder theory from the perspective of toilet hygiene in public sector management, statistically chart and analyse the TCI using pertinent toilet attribute variables, create an action plan involving different approaches to motivate public toilet owners to work on long-term improvements, evaluate the risk-return trade-offs of such a plan, and get engaged in an interactive Statistical Hands-on Workshop.